(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
The main goal of organizing and developing students’ research work is to increase the level of scientific training of specialists with higher professional education. Students’ research work is a continuation and deepening of the educational process. Research work develops their creativity, skills and abilities, and increases their motivation to study the taught sciences.